2022
DOI: 10.1002/rse2.270
|View full text |Cite
|
Sign up to set email alerts
|

The development of an unsupervised hierarchical clustering analysis of dual‐polarization weather surveillance radar observations to assess nocturnal insect abundance and diversity

Abstract: Contemporary analyses of insect population trends are based, for the most part, on a large body of heterogeneous and short-term datasets of diurnal species that are representative of limited spatial domains. This makes monitoring changes in insect biomass and biodiversity difficult. What is needed is a method for monitoring that provides a consistent, high-resolution picture of insect populations through time over large areas during day and night. Here, we explore the use of X-band weather surveillance radar (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“…A comparison with ground sampling confirmed that the identified target classes were ecologically meaningful; i.e. the number of target classes observed on radar correlated well with macro-moth diversity on the ground [ 73 ]. While the taxonomic resolution is still coarse, differentiating broad groups of aerial taxa may also be useful in itself, e.g.…”
Section: Current State Of Radar-based Biodiversity Monitoring Of Insectsmentioning
confidence: 99%
See 2 more Smart Citations
“…A comparison with ground sampling confirmed that the identified target classes were ecologically meaningful; i.e. the number of target classes observed on radar correlated well with macro-moth diversity on the ground [ 73 ]. While the taxonomic resolution is still coarse, differentiating broad groups of aerial taxa may also be useful in itself, e.g.…”
Section: Current State Of Radar-based Biodiversity Monitoring Of Insectsmentioning
confidence: 99%
“…While the taxonomic resolution is still coarse, differentiating broad groups of aerial taxa may also be useful in itself, e.g. for interactions between insects and insectivores [ 73 ].…”
Section: Current State Of Radar-based Biodiversity Monitoring Of Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radars have a long history of use in monitoring animals in the air [19,20], have been extensively validated [21,22], and weather radar has become a standard tool to quantify bird migration [23,24]. Novel methods are rapidly being developed to adapt weather radar for quantitative entomological applications [25,26], with recent studies using weather radar to quantify mayfly emergence [27], monitor pest exodus flights [28], and differentiate classes of insects [29]. Weather radar only observes insects in flight in the free airspace (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning radars further have the potential to cover spatially large regions. During recent years, the deployment of specialized radar-based detection methods for aerial fauna has become more prevalent, especially for movements of up to several hundred meters up in the air (e.g., Hu et al 2016, Lukach et al 2022, Wainwright et al 2023, Haest et al 2024b, Bauer et al 2024). To study larger flying animals, like birds and bats, radar instruments with wavelengths of a few up to several centimeters, like X-band (λ = 2.5-3.75 cm; e.g.…”
Section: Introductionmentioning
confidence: 99%